The wedding quilt bride - Perry, Marta (Love inspired., 2018)
"Widow Rebecca Mast returns to her Amish community with her son and a dream--to own a quilt shop. Carpenter Daniel King is determined to help Rebecca and revive their childhood friendship. But as he bonds with her son, Rebecca's afraid the secret she's been keeping will be revealed. Can Daniel convince Rebecca he's a man she can trust--and love?" -- Page [4] cover.